Delay in development and behavioural abnormalities in the absence of p53 in zebrafish - Elabd, Seham; Jabeen, Nuzhat Amna; Gerber, Vanessa; Peravali, Ravindra; Bourdon, Jean-Christoph; Kancherla, Shilpa; Vallone, Daniela; Blattner, Christine (PloS one, 2019)
p53 is well-known for its tumour-suppressive activity. However, in the past decade it became clear that p53 is also involved in other processes including stem cell proliferation, differentiation and animal development. To investigate the role of p53 in early embryonic development, we targeted p53 by CRISPR/Cas9 to make a p53 knock-out zebrafish (Danio rerio). Our data show developmental and behavioural effects in p53-deficient zebrafish embryos and larvae. Specifically, we found that early development of zebrafish was clearly delayed in the absence of p53. However, after 1 day (1 dpf), the p53-deficient embryos appeared to recover, as evidenced by a similar level of pigmentation at 26 hpf, similar size of the eye at 4 dpf and only a minor difference in body size at 4 dpf compared to p53 wild-type siblings. The recovery of development after 1 dpf in p53-deficient embryos could be due to a compensatory mechanism involving other p53 family members. p63 and p73 were found over-expressed with respect to wild-type siblings. However, despite this adaptation, the hatching time remained delayed in p53-/- zebrafish. In addition to differences in development, p53-null zebrafish embryos also showed differences in behaviour. We observed an overall reduced activity and a reduced travel distance under non-stressed conditions and after exposing the larvae to vibration. We also observed a longer latency until the larvae started to move after touching with a needle. Overall, these data indicate that p53 is involved in early development and locomotion activities.